The effect of exercise induced glycogen depletion on the lactate, ventilatory and electromyographic thresholds - Glass, C.; Knowlton, R. G.; Sanjabi, P. B.; Sullivan, J. J. (The Journal of Sports Medicine and Physical Fitness, 1997)
BACKGROUND: This study compared the integrated electromyogram (IEMG), lactate, and ventilatory thresholds under normal glycogen (NG) and depleted glycogen (DG) conditions for the purpose of determining the presence of a possible relationship between neuromuscular, metabolic and respiratory thresholds. MATERIALS AND METHODS: Six trained, male cyclists (Age = 24.0 +/- 2.45 yrs, Ht = 1.76 +/- 0.84 m, Mass = 76.22 +/- 10.03 kg, % Fat = 8.57 +/- 1.50, VO2 peak = 68.97 +/- 10.46 ml . kg-1 . min-1) completed a progressive, incremental cycle ergometer test under NG and DG conditions in a randomized order. Glycogen depletion was accomplished by having the subjects: (1) engage in a 12 hour fast prior to the exercise test, (2) complete a 1.5 hour ride at their ventilatory threshold, and (3) complete 4 to 8 one-minute rides at 100% of VO2 peak. Six hours following the depletion rides, the subjects completed the exercise test (90 rpm, 45 watts/2 min). Blood was withdrawn through a forearm venous catheter each minute and later analyzed for blood lactate. Metabolic data were measured every 30s and the IEMG of the rectus femoris was recorded during the last 10s of each minute of the exercise test. Results showed that under NG, the IEMG (TIEMG), lactate (Tlac), and ventilatory (Tvent) thresholds occurred at a similar VO2 (TIEMG = 3.46 +/- 0.31, Tlac = 3.51 +/- 0.34, Tvent = 3.36 +/- 0.42 L . min-1). However, under DG there was a significant shift in the TIEMG to a higher VO2 (TIEMG = 4.41 +/- 0.54 L . min-1 = p 0.003). Tlac was not significantly greater following glycogen depletion, but had shifted to a higher VO2 in relation to the Tvent (Tlac = 3.96 +/- 0.40 L . min-1, Tvent = 3.37 +/- 0.64 L . min-1 = p 0.01). These data show that lactate accumulation and muscle activation of the vastus lateralis and rectus femoris are not the controlling mechanisms of the ventilatory threshold during progressive, incremental cycling exercise.